Islamic Finance Industry and Fintech: A Comparative Analysis - Madouri Hadda; Bouchelit Rym (المجلة الدولية للأداء الاقتصادي)
This article examines the effects of fin-tech on Islamic finance in both OIC and non-OIC countries. It finds that Islamic finance grows faster in OIC countries due to supportive regulations, while fin-tech enhances accessibility and efficiency in non-OIC countries. The research underscores the importance of regulatory frameworks in optimising fintech's impact. Though it relies on existing data, the study offers useful insights for policymakers and financial institutions. This emphasises the capacity of fin-tech to enhance financial inclusivity and promote socio-economic progress. The research stands out for its comparative methodology, which offers fresh perspectives on the interplay between fin-tech and Islamic finance across different regional contexts.